2021
DOI: 10.1088/2053-1591/abf682
|View full text |Cite
|
Sign up to set email alerts
|

Possible negative correlation between electrical and thermal conductivity in p-doped WSe2 single crystal

Abstract: The materials with high electrical conductivity σ and low thermal conductivity κ are the driving force for an efficient thermoelectric device. In general, electrical and thermal conductivity cannot be controlled independently as both electron and phonon participate in transport processes. Two dimensional layered materials are one such kind where van der Waals inter-layer interaction and covalent intra-layer bond favours strong phonon mediated electronic interaction. Here, we report that the substitutional p-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…At room temperature, WSe 2 exhibits a σ of 0.01 S/m, whereas the superlattice displays an elevated value of 0.39 S/m, attributed to its four times higher mobility in comparison to WSe 2 . Notably, the calculated electrical conductivity of WSe 2 at 600 K, 70.85 S/m, with a calculated carrier concentration of 10 19 cm –3 , closely aligns with experimental findings (80 S/m) . In both materials, the conductivity of electrons surpasses that of holes, which is attributed to distinct curvatures of valence and conduction bands near the Fermi level.…”
Section: Resultssupporting
confidence: 86%
“…At room temperature, WSe 2 exhibits a σ of 0.01 S/m, whereas the superlattice displays an elevated value of 0.39 S/m, attributed to its four times higher mobility in comparison to WSe 2 . Notably, the calculated electrical conductivity of WSe 2 at 600 K, 70.85 S/m, with a calculated carrier concentration of 10 19 cm –3 , closely aligns with experimental findings (80 S/m) . In both materials, the conductivity of electrons surpasses that of holes, which is attributed to distinct curvatures of valence and conduction bands near the Fermi level.…”
Section: Resultssupporting
confidence: 86%
“…It can be observed that all four films feature high carrier concentrations in the order of 10 18 to 10 20 cm -3 . These are significantly larger than those typically reported for TMDCs 41,43 and contribute to the high conductivities measured for the films. Such high carrier concentration is likely due to the formation of vacancies at the chalcogenide site on Please do not adjust margins Please do not adjust margins the crystallite surface.…”
Section: Electrical Characterisationcontrasting
confidence: 54%
“…63 In this work, despite the films all being found to be in the 2H coordination (illustrated by the XRD and the Raman spectra), all films yielded a strikingly high electrical conductivity when compared to literature. 41,64–66…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations